1996
DOI: 10.1016/0304-3959(96)03128-4
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic obturator nerve block for inguinal and back pain: a recovered opinion

Abstract: Peripheral nerve blocks are very useful in diagnosing certain pain conditions. We report a case of chronic inguinal and back pain secondary to hip arthropathy. An obturator nerve block was used to help determine the origin of the pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 2 publications
0
11
0
1
Order By: Relevance
“…Probably because it is a timeconsuming and, without guidance, an operator-dependent technique [6,8], it has not been widely used. Pain relief due to surgical dissection or manual percutaneous block of the obturator nerve without imaging guidance has been reported before with varying success [4,5,7,14,15,16]. Computed tomographic guidance, however, allows easy, fast and reproducible access to the obturator nerve.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Probably because it is a timeconsuming and, without guidance, an operator-dependent technique [6,8], it has not been widely used. Pain relief due to surgical dissection or manual percutaneous block of the obturator nerve without imaging guidance has been reported before with varying success [4,5,7,14,15,16]. Computed tomographic guidance, however, allows easy, fast and reproducible access to the obturator nerve.…”
Section: Discussionmentioning
confidence: 96%
“…In addition to this application, ONB has been used by anaesthesiologists for relief of adductor muscle contraction in patients with paraplegia or multiple sclerosis, and in few studies its use for diagnosis and treatment of painful conditions of the hip joint has been described [4,5,6,7,8]. Reported results have varied and the procedure has not been widely used for treatment of hip pain.…”
Section: Introductionmentioning
confidence: 98%
“…To diagnose the origin of the pain in the hip region, hip block with local anesthetics has been advocated. [4][5][6][7][8] Crawford et al 4 investigated the efficacy of intraarticular injection of local anesthetics in 42 patients with primary osteoarthritis of the hip and showed that the injection of local anesthetics into the hip was a reliable diagnostic tool. Several investigators indicated the usefulness of peripheral nerve block of the obturator nerve or nerves to quadratus femoris as a diagnostic and therapeutic tool for patients with hip joint pain.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators indicated the usefulness of peripheral nerve block of the obturator nerve or nerves to quadratus femoris as a diagnostic and therapeutic tool for patients with hip joint pain. 5,6 Hong et al 8 reported a case of chronic inguinal and back pain secondary to hip arthropathy in which an obturator nerve block was successfully used to determine the origin of the pain. In our cases, we confirmed that the pain was attributed to the hip joint using intra-articular injections of local anesthetics or articlular branch blocks of the obturator nerve.…”
Section: Discussionmentioning
confidence: 99%
“…De manière plus spécifique, on peut observer des risques de perforation digestive mais qui reste très théorique car il y a un contrôle tomodensitométrique, de chute du fait d'une atteinte des muscles adducteurs [21,22].…”
Section: Complicationsunclassified